MAP OF DA'WAH BLIMBING VILLAGE, PACIRAN DISTRICT, LAMONGAN REGENCY, EAST JAVA PROVINCE - Sya'roni Tohir; Trio Satrio Kurniawan (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
To find out the Da'wah Map of Blimbing Village, Paciran District, Lamongan Regency in 2022. Research Method: Qualitative. Research Results: From the SWOT analysis, preaching in Blimbing has several opportunities, threats, strengths and weaknesses, including: (low opportunity) a consumptive society, (moderate opportunity) the need for free education and a modernizing society, (best opportunity) the majority Muslim religion, requires true Islamic teachings, is egalitarian, welcome, enthusiastic, as well as adequate means of proselytizing, (major threat) religious and community sentiments that are inclusive, (moderate threat) there is competition between institutions, (minor threat) the community heterogeneous, (strength) da'wah can be carried out openly and comprehensively, and (weaknesses) the lack of preachers and their quality, as well as the lack of maximizing the power of da'wah. Conclusion: Da'wah in Blimbing Village is carried out actively and organized through proselytizing organizations/institutions as well as programs of existing religious facilities. Adequate facilities include mosques and prayer rooms, formal and diniyah educational institutions, as well as various community charities to support da'wah. However, the da'wah that has been carried out has not been maximized, so efforts are needed to improve weaknesses, take advantage of opportunities, and minimize threats to become strengths of da'wah.